A new method for fatigue life prediction based on the Thick Level Set approach. (September 2017) - Voormeeren, L.O.; van der Meer, F.P.; Maljaars, J.; Sluys, L.J.
Highlights: Thick Level Set extended to interfaces as a new method for fatigue life prediction. Fatigue crack growth result of interaction between damage and fracture mechanics. Global fracture parameters act as driving force for fatigue crack growth (Paris). Fatigue model applicable to a range of materials due to interface formulation. Abstract: The last decade has seen a growing interest in cohesive zone models for fatigue applications. These cohesive zone models often suffer from a lack of generality and applying them typically requires calibrating a large number of model-specific parameters. To improve on these issues a new method has been proposed in this paper based on the Thick Level Set approach. In this concept, material degradation due to cyclic loading is the result of interaction between damage evolution and fracture mechanics. The Thick Level Set formulation has been extended to interface elements, in order to allow for separation of strain energy in the bulk and energy required for surface creation. Global fracture parameters, derived from a free energy description governing the interface elements, are used as input for the empirical crack growth rate relation (Paris' equation). It must be emphasized that in contrast to existing fatigue models, the Thick Level Set approach does not require the definition of a damage evolution law. Instead, damage is updated automatically by a continuously moving damage front. It is shown that applicability is not limited to fatigue behavior of linear elastic materials; elastic-plastic materials such as steels can be analysed as well. The sensitivity of model parameters is investigated and discussed and the practical relevance is explored for standard test configurations.